PERBANDINGAN PENGELOLAAN SAMPAH DI NEGARA INDONESIA DAN NEGARA SINGAPURA - Galuh, Galuh Lalita Paramarta; Sunarno, (Jurnal Hukum Positum, 2024)
In Indonesia, especially Banyumas Regency, the Regional Government of Banyumas Regency makes policies regarding existing waste management, these various policies are contained in Banyumas Regent Regulation Number 24 of 2023 concerning the Implementation of Waste Management. Apart from that, Singapore also implements various policies related to waste management, such as burning waste and managing food waste. This research is important to carry out because it is to find out how waste management compares in Indonesia and Singapore. The method used is empirical legal research through interviews and literature study. The results of this research are that waste management in Indonesia, especially in Banyumas Regency and Singapore, is both running well and is carried out in different ways. The conclusion in this research is that various programs and policies have been implemented in Indonesia, especially Banyumas Regency and Singapore, which have both been implemented well and the government has taken concrete steps to overcome the problem of waste management in these two countries.